Mummy with no name - "Stilton, Geronimo" (New York, 2005)
Enter the world of Geronimo Stilton, where another funny adventure is always right around the corner. Each book is a fast-paced adventure with lively art and a unique format kids 7-10 will love. Halloween and Egypt and mummies . . . oh, my! I admit it, I am a 'fraidy mouse. Halloween scares me out of my fur! But this Halloween, I was heading off on an adventure in one of my very favorite places: Egypt. I couldn't wait to see the sights and soak up some sun far away from New Mouse City. What I didn't realize was that Halloween is popular in Egypt, too -- with the mummies, that is! Oh, what's a 'fraidy mouse to do?
Keywords: Children book